Care Poverty Within the Home Space: Exploring the Emotional Experiences of Unmet Care Needs - Sihto, Tiina; Van Aerschot, Lina (Frontiers in Sociology, 2021)
Older adults face inequalities in care. The concept of care poverty has been developed to point out how unmet care needs are not just an individual issue but a phenomenon linked to social and economic disadvantage and societal inequality. In this paper, we approach the question of care poverty by focusing on its intertwinement with emotions and the home space. We analyze how the presence, or more commonly absence, of care shapes interviewees’ descriptions of emotional experiences tied to the home space. Our data consists of 12 semi-structured interviews conducted in 2019 and 2020 with customers of outreach work for older adults in Finland. These customers typically face a situation that can be characterized as care poverty: their care needs are not (or have not been) met by either the service system or informal sources. When analyzing the data, we followed the guidelines for thematic analysis proposed by Braun and Clarke. Our analysis shows how care and lack of care transform interviewees’ emotional connections with the home space, highlighting particularly three main themes: insecurity, isolation and belongingness. Our analysis reveals how lack of care can transform the home into an unsafe place; a space characterized by isolation, or a space where one sometimes ceases to feel at ease or “like oneself.” The emotional experience of home and being adequately cared for is also tied to the sense of (not) belonging to a place. Based on our analysis, we argue that as an experience, care poverty is not just about individual unmet needs and/or a scarcity of resources at the societal level; it should also be understood as deeply relational—born and shaped in interactions (or the lack of interactions) among people, and lived in and through relationships with others. Furthermore, we highlight the importance of a sense of belonging to the feeling of being adequately cared for.